Quenching pretreatment coal derived hard carbon negative electrode material as well as preparation and application thereof

By quenching pretreatment and pyrolytic carbonization treatment on coal-derived hard carbon materials, the problem of insufficient sodium storage capacity and rate performance of coal-derived hard carbon in sodium ion batteries is solved, and efficient and stable sodium ion battery performance is achieved.

CN119858908AActive Publication Date: 2025-04-22XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510098006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-22
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Among existing sodium ion batteries, coal-derived hard carbon has few sodium storage active sites, low capacity and poor rate performance, making it difficult to meet the commercial needs of sodium ion batteries.

Method used

The coal precursor particles and pyrolysis intermediates are impregnated with liquid nitrogen to change their microstructure, and then pyrolysis and high-temperature carbonization are carried out to form a hard carbon material with high sodium storage capacity and good rate performance.

Benefits of technology

It significantly improves the first-effect, reversible capacity and cycling performance of sodium ion batteries, provides more sodium storage sites and diffusion channels, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253380100000081
    Figure BDA0005253380100000081
  • Figure HDA0005253380110000011
    Figure HDA0005253380110000011
  • Figure HDA0005253380110000012
    Figure HDA0005253380110000012
Patent Text Reader

Abstract

The invention discloses a quenching pretreated coal derived hard carbon negative electrode material as well as preparation and application thereof. The method comprises the following steps: acquiring a coal precursor; performing first-stage low-temperature pyrolysis on the coal particles to obtain a carbon intermediate; performing second-stage high-temperature carbonization on the carbon intermediate to obtain hard carbon; wherein the coal precursor and / or the carbon intermediate are / is subjected to shock cooling pretreatment. Through the method, a new channel and sufficient sodium storage active sites are provided for effective diffusion and embedding of sodium ions while it is ensured that the pseudo-graphitized structure hard carbon has high conductivity, migration and storage of the sodium ions are remarkably improved, and finally the coal-based sodium ion battery hard carbon negative electrode material with high efficiency and high capacity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a hard carbon negative electrode material derived from quenched pretreated coal, and a preparation method and application thereof. Background Art

[0002] As the proportion of renewable energy in electricity increases year by year, large-scale, low-cost energy storage technology has become a bottleneck for renewable energy grid connection. In recent years, problems such as price fluctuations of lithium resources, limited lithium reserves, and combustion and explosion of lithium-ion batteries have become prominent. It is urgent to develop safe, low-cost, and large-scale energy storage technology. Sodium-ion batteries have abundant sodium resources, similar working principles to lithium-ion batteries, and do not involve safety issues caused by dendrite growth. They are considered to be one of the ideal large-scale energy storage technologies. However, one of the main reasons for the lag in the industrialization of sodium-ion batteries is the lack of high-performance, low-cost negative electrode materials that can be produced on a large scale. Hard carbon has abundant precursor resources, high reversible capacity, and high platform capacity in the low potential range. It is considered to be the most promising negative electrode material for sodium-ion batteries. The precursors of hard carbon mainly include biomass, oxygen-containing resins, asphalt, and coal. Among them, coal has the characteristics of being rich in carbon, easy to regulate, and abundant in reserves, and is one of the more ideal low-cost precursors of hard carbon. However, the high aromaticity of coal makes its structure dense and its porosity reduced during high-temperature carbonization, resulting in fewer sodium storage active sites, low capacity, and poor rate performance of coal-derived hard carbon.

[0003] In order to solve the above problems, methods such as activation, oxidation, and coating have been developed to improve the sodium storage performance of coal-based hard carbon, but the above methods have certain problems in cost or effect. It is urgent to develop cheap and efficient modification methods to meet the requirements of sodium ion battery commercialization. Summary of the invention

[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a hard carbon negative electrode material derived from quenched pretreated coal.

[0005] Another object of the present invention is to provide a quenched pretreated coal-derived hard carbon negative electrode material obtained by the above preparation method.

[0006] Another object of the present invention is to provide the use of the above-mentioned quenched pretreated coal-derived hard carbon negative electrode material in sodium ion batteries.

[0007] The quenched pretreated coal-derived hard carbon negative electrode material is applied to the negative electrode of a sodium ion battery and exhibits the advantages of high sodium storage capacity, good rate performance, stable cycle performance, etc.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a hard carbon negative electrode material derived from quenched pretreated coal comprises the following steps:

[0010] (1) crushing, screening, washing and drying the coal raw material to obtain coal precursor particles;

[0011] (2) pyrolyzing the coal precursor particles at low temperature to obtain a pyrolysis intermediate;

[0012] (3) carbonizing the pyrolysis intermediate at high temperature to obtain a hard carbon material;

[0013] The coal precursor particles obtained in step (1) and / or the pyrolysis intermediate obtained in step (2) need to be subjected to quenching pretreatment.

[0014] Preferably, the coal raw material in step (1) is at least one of lignite and bituminous coal.

[0015] Preferably, in step (1), the coal raw material is crushed and sieved to obtain raw coal particles with a particle size of 0.5 to 500 μm.

[0016] Preferably, the washing in step (1) refers to first acid washing and then water washing to neutrality.

[0017] More preferably, the pickling refers to pickling with a 0.1 to 5 mol / L hydrochloric acid solution for 1 to 120 hours.

[0018] Preferably, the pyrolysis temperature in step (2) is 200-900°C; more preferably 300-800°C; most preferably 600-800°C.

[0019] Preferably, the pyrolysis time in step (2) is 1 to 6 hours; more preferably 1 to 2 hours; most preferably 2 hours.

[0020] Preferably, the heating rate of the pyrolysis in step (2) is 1 to 50°C / min; more preferably 5 to 20°C / min; most preferably 10°C / min.

[0021] Preferably, the pyrolysis in step (2) and the carbonization in step (3) are carried out under an inert atmosphere, and the inert atmosphere is at least one of nitrogen, argon and helium.

[0022] Preferably, the carbonization temperature in step (3) is 900-1800°C; more preferably 1100-1400°C; most preferably 1200-1400°C.

[0023] Preferably, the carbonization time in step (3) is 1 to 30 hours; more preferably 2 to 3 hours; most preferably 2 hours.

[0024] Preferably, the heating rate of the carbonization in step (3) is 1 to 50°C / min; more preferably 2 to 5°C / min; most preferably 2°C / min.

[0025] Preferably, the temperature of the quench pretreatment is -300 to 0°C; more preferably -300 to -180°C; most preferably liquid nitrogen quench pretreatment.

[0026] Preferably, the quenching pretreatment time is 1 min to 3000 min; more preferably 10 to 30 h; most preferably 15 to 30 h.

[0027] The present invention provides a hard carbon negative electrode material derived from quenched pretreated coal prepared by the above preparation method.

[0028] The present invention also provides the use of the above-mentioned quenched pretreated coal-derived hard carbon negative electrode material in a sodium ion battery.

[0029] Generally, the carbon layers of coal are easily rearranged and stacked during the direct high-temperature carbonization process, resulting in coal-based carbon materials showing highly ordered microcrystalline structures, small interlayer spacing and low porosity, which limits the embedding of sodium ions. Today, most researchers have proposed activation, oxidation, coating and other methods to improve the electrochemical properties of coal-based carbon materials, but these improvement processes are complex and time-consuming, and it is difficult to meet the requirements of the commercialization of sodium-ion batteries. The temperature difference of more than 200°C between liquid nitrogen (-196°C) and coal can be used to produce a strong "cold shock" effect on coal, inducing the expansion of interlayer spacing and pore structure, inhibiting the high degree of graphitization in the subsequent carbonization process, and bringing high sodium storage performance.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] (1) The present invention provides a method for preparing coal-derived hard carbon negative electrode materials for sodium ion batteries by quenching pretreatment. First, the precursor particles and / or pyrolysis intermediates are impregnated with liquid nitrogen, which causes many cracks and channels to form on the surface of the material, changing its microstructure. Secondly, after undergoing low-temperature pyrolysis and high-temperature carbonization processes, the carbon layer is rearranged, and some open pores are closed to form closed pores, revealing more pseudo-graphite domain structures and surface defects, providing new channels and sodium storage sites for the effective diffusion and embedding of sodium ions, which is beneficial to the rapid migration and storage of sodium ions, thereby greatly improving the first efficiency, reversible capacity and cycle performance of sodium ion batteries.

[0032] (2) The present invention performs quenching pretreatment on the precursor particles and the pyrolysis intermediates respectively, and compares the effects of the "cold shock" effect at different stages on the final carbon material structure, indicating that impregnation of the intermediates is more conducive to the formation of pseudo-graphite domain structure and closed-pore structure.

[0033] (3) The preparation process provided by the present invention is relatively simple and green, suitable for large-scale industrial production; the product performance is relatively good and has certain competitive advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the hard carbon material obtained in Example 4.

[0035] Figure 2 This is the X-ray diffraction pattern of the hard carbon material obtained in Example 4.

[0036] Figure 3 This is the Raman image of the hard carbon material obtained in Example 4.

[0037] Figure 4 This is the charge and discharge curve of the hard carbon material obtained in Example 4.

[0038] Figure 5 This is the long cycle diagram of the hard carbon material obtained in Example 4. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0040] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0041] The preparation method of the coal precursor particles described in the examples and comparative examples of the present application is as follows:

[0042] (1) crushing and screening the lignite by a crushing device to obtain lignite particles with a particle size of 74 μm;

[0043] (2) washing the raw coal particles after crushing and screening, acid washing them with 2 mol / L hydrochloric acid for 12 hours, and then washing them with water until they are neutral;

[0044] (3) Drying the acid-washed coal to obtain precursor particles.

[0045] Comparative Example 1

[0046] (1) Preparation of coal precursor particles.

[0047] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the coal precursor particles are heated from room temperature to 600° C. at a heating rate of 10° C. / min, and kept at this temperature for 2 h to obtain a pyrolysis intermediate.

[0048] (3) The above sample was placed in a tubular furnace under a nitrogen atmosphere, and the temperature was increased to 1300°C at a heating rate of 2°C / min and maintained at the constant temperature for 2 h to obtain a hard carbon material.

[0049] Example 1

[0050] (1) Preparation of coal precursor particles.

[0051] (2) The coal precursor particles are immersed in liquid nitrogen for 10 hours and then dried in an oven at 80° C. to obtain a quenched pretreated coal precursor.

[0052] (3) The dried quenched pretreated coal precursor is placed in a tubular furnace under a nitrogen atmosphere for the first stage of pyrolysis treatment, where the coal precursor particles are heated from room temperature to 800°C at a heating rate of 10°C / min and kept at that temperature for 2.5 hours to obtain a carbon intermediate.

[0053] (4) The sample was placed in a tubular furnace under a nitrogen atmosphere for the second carbonization step. The temperature was increased to 1100°C at a heating rate of 2°C / min and maintained at this temperature for 3 h to obtain a hard carbon material.

[0054] Example 2

[0055] (1) Preparation of coal precursor particles.

[0056] (2) The coal precursor particles are immersed in liquid nitrogen for 10 hours and then dried in an oven at 80° C. to obtain a quenched pretreated coal precursor.

[0057] (3) The dried quenched pretreated coal precursor is placed in a tubular furnace under a nitrogen atmosphere for the first stage of pyrolysis treatment, where the coal precursor particles are heated from room temperature to 600°C at a heating rate of 5°C / min and kept at this temperature for 2.5 hours to obtain a carbon intermediate.

[0058] (4) The sample was placed in a tubular furnace under a nitrogen atmosphere for the second carbonization step. The temperature was increased to 1300°C at a heating rate of 2°C / min and maintained at this temperature for 2 h to obtain a hard carbon material.

[0059] Example 3

[0060] (1) Preparation of coal precursor particles.

[0061] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the coal precursor particles are heated from room temperature to 700°C at a heating rate of 5°C / min and kept at this temperature for 2.5 hours to obtain a pyrolysis intermediate.

[0062] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 15 h, and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0063] (4) The quenched pretreated intermediate was placed in a tubular furnace under a nitrogen atmosphere, heated to 1300°C at a heating rate of 3°C / min, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0064] Example 4

[0065] (1) Preparation of coal precursor particles.

[0066] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the precursor particles are heated from room temperature to 600°C at a heating rate of 10°C / min and kept at this temperature for 2 h to obtain a pyrolysis intermediate.

[0067] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 15 h, and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0068] (4) The quenched pretreated intermediate was placed in a tubular furnace under a nitrogen atmosphere, heated to 1200°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0069] Example 5

[0070] (1) Preparation of coal precursor particles.

[0071] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the coal precursor particles are heated from room temperature to 400°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain a pyrolysis intermediate.

[0072] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 15 h, and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0073] (4) The quenched pretreated intermediate was placed in a tubular furnace under a nitrogen atmosphere, heated to 1500°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0074] Example 6

[0075] (1) Preparation of coal precursor particles.

[0076] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the coal precursor particles are heated from room temperature to 600°C at a heating rate of 10°C / min and kept at this temperature for 2 hours to obtain a pyrolysis intermediate.

[0077] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 30 hours and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0078] (4) The quenched pretreated intermediate was placed in a tubular furnace under a nitrogen atmosphere, heated to 1400°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0079] Example 7

[0080] (1) Preparation of coal precursor particles.

[0081] (2) The coal precursor particles are placed in a tubular furnace under a nitrogen atmosphere, and the coal precursor particles are heated from room temperature to 600°C at a heating rate of 10°C / min and kept at this temperature for 2 hours to obtain a pyrolysis intermediate.

[0082] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 30 hours and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0083] (4) The quenched pretreated intermediate was placed in a tubular furnace under a nitrogen atmosphere, heated to 1300°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0084] Example 8

[0085] (1) Preparation of coal precursor particles.

[0086] (2) The coal precursor particles are placed in a tubular furnace, and in a nitrogen atmosphere, the coal precursor particles are heated from room temperature to 300° C. at a heating rate of 3° C. / min, and kept at this temperature for 2 h to obtain a pyrolysis intermediate.

[0087] (3) The pyrolysis intermediate was immersed in liquid nitrogen for 30 hours and then dried in an oven at 80° C. to obtain a quenched pretreated intermediate.

[0088] (4) The quenched pretreated intermediate was placed in a tubular furnace, and heated to 1200°C at a heating rate of 2°C / min under a nitrogen atmosphere, and kept at this temperature for 2 hours to obtain a hard carbon material.

[0089] Electrochemical performance test

[0090] The hard carbon negative electrode material prepared in Comparative Example 1 and Examples 1 to 8 was used as the working electrode, sodium was used as the counter electrode, the electrolyte was a sodium hexafluorophosphate solution (the concentration of sodium hexafluorophosphate was 0.8 mol / L, and the solvent was a mixed solution of ethylene carbonate EC and diethyl carbonate DEC in a volume ratio of 1:1), and button cells were assembled. The voltage range was 0.001-2.5 V at a current density of 20 mA / g using a blue electric tester, and the test results are shown in Table 1.

[0091] Table 1

[0092]

[0093] As can be seen from Table 1, the hard carbon negative electrode prepared in Example 4 exhibits the best charge-discharge specific capacity and first coulomb efficiency. The use of liquid nitrogen for quenching pretreatment forms many cracks and channels on the surface of the material, changing its microstructure. Secondly, after low-temperature pyrolysis and high-temperature carbonization processes, the carbon layer is rearranged, and some open pores are closed to form closed pores, showing more pseudo-graphite domain structures and surface defects, providing new channels for the effective diffusion of sodium ions, and providing additional active sites for the storage of sodium ions, which comprehensively improves the rate, capacity and cycle performance of the negative electrode of the sodium ion battery.

[0094] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material derived from quenched pretreated coal, characterized in that: The following steps are involved: (1) crushing, screening, washing and drying the coal raw material to obtain coal precursor particles; (2) pyrolyzing the coal precursor particles at 200-900° C. to obtain a pyrolysis intermediate; (3) carbonizing the pyrolysis intermediate at 900-1800° C. to obtain a hard carbon material; The coal precursor particles obtained in step (1) and / or the pyrolysis intermediate obtained in step (2) need to be pre-treated by quenching at -300 to 0°C for 1 to 3000 minutes.

2. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 1, characterized in that: The temperature of the quenching pretreatment is -300 to -180°C; And / or, the quenching pretreatment time is 10 to 30 hours; And / or, the coal raw material in step (1) is at least one of lignite and bituminous coal.

3. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 2, characterized in that: The quenching pretreatment is liquid nitrogen quenching pretreatment; And / or, the quenching pretreatment time is 15 to 30 hours.

4. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 1 or 2, characterized in that: The pyrolysis temperature in step (2) is 300-800°C; And / or, the pyrolysis time in step (2) is 1 to 6 hours; And / or, the heating rate of the pyrolysis in step (2) is 1 to 50°C / min.

5. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 4, characterized in that: The pyrolysis temperature in step (2) is 600-800° C. And / or, the pyrolysis time in step (2) is 1 to 2 hours; And / or, the heating rate of the pyrolysis in step (2) is 5 to 20°C / min.

6. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 1 or 2, characterized in that: The carbonization temperature in step (3) is 1100-1400° C. And / or, the carbonization time in step (3) is 1 to 30 hours; And / or, the heating rate of the carbonization in step (3) is 1 to 50°C / min.

7. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 6, characterized in that: The carbonization temperature in step (3) is 1200-1400° C. And / or, the carbonization time in step (3) is 2 to 3 hours; And / or, the heating rate of the carbonization in step (3) is 2 to 5°C / min.

8. The method for preparing a hard carbon negative electrode material derived from quenched pretreated coal according to claim 1 or 2, characterized in that: In step (1), the coal raw material is crushed and sieved to obtain raw coal particles with a particle size of 0.5 to 500 μm; And / or, the washing in step (1) refers to first acid washing and then water washing until neutral; And / or, the pickling refers to pickling with a 0.1 to 5 mol / L hydrochloric acid solution for 1 to 120 hours; And / or, the pyrolysis in step (2) and the carbonization in step (3) are carried out under an inert atmosphere, and the inert atmosphere is at least one of nitrogen, argon and helium.

9. A hard carbon negative electrode material derived from quenched pretreated coal obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the hard carbon negative electrode material derived from quenched pretreated coal as claimed in claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of large-layer-spacing graphite anode material of sodium-ion battery

    CN105720269A

  • Preparation method of biomass sodium ion battery negative electrode

    CN115101723A

  • Regenerated graphite negative electrode active material as well as preparation and application thereof

    CN117125708A

  • Carbon material

    JP2016056038A